2010
DOI: 10.1016/j.ejcts.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lung ischaemia–reperfusion induced gene expression

Abstract: Large numbers of genes relating to cell metabolism, transcription control, inflammation and apoptosis were significantly up- and down-regulated following controlled ventilation and early lung ischaemia-reperfusion, consistent with previous studies. In addition, novel genes related to lung injury were identified. These genetic signatures provide new insights into early molecular mechanisms of ischaemia-reperfusion lung injury and help refine therapeutic strategies to lessen pulmonary dysfunction following cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…This was confirmed at the protein level with an increase in LCN2 and a decrease in CXCL10 in mice subjected to hypoxia-reoxygenation. In concordance with these results, downregulation of inflammatory genes has been reported after ischemia-reperfusion in adult rats [16], while another study reported increased expression of inflammatory genes [11]. Previously, we have reported both unaltered [8] and increased inflammatory markers [7] after hypoxia-reoxygenation in neonatal pigs, and upregulated Lcn2 after hypoxia-reoxygenation in mice [9].…”
Section: Discussionsupporting
confidence: 75%
“…This was confirmed at the protein level with an increase in LCN2 and a decrease in CXCL10 in mice subjected to hypoxia-reoxygenation. In concordance with these results, downregulation of inflammatory genes has been reported after ischemia-reperfusion in adult rats [16], while another study reported increased expression of inflammatory genes [11]. Previously, we have reported both unaltered [8] and increased inflammatory markers [7] after hypoxia-reoxygenation in neonatal pigs, and upregulated Lcn2 after hypoxia-reoxygenation in mice [9].…”
Section: Discussionsupporting
confidence: 75%
“…PubMed was searched for all messenger RNA (mRNA) microarray studies describing significantly upregulated gene expression in nonfetal lung cells or tissue in the setting of ALI, acute respiratory distress syndrome, pulmonary ischemia‐reperfusion, and/or primary pulmonary graft dysfunction. A total of 31 gene lists including 843 unique genes were identified from 23 articles . Based on the experimental models used in each study, these gene lists were subdivided into one of 3 “mechanical/noninfectious” categories (ischemia‐reperfusion, stretch, primary graft dysfunction) or one of 3 “toxic/infectious” categories (infection, sepsis, toxicity).…”
Section: Methodsmentioning
confidence: 99%
“…Genome‐wide microarray studies have previously demonstrated that ALI induces coordinated changes in the expression of hundreds of genes . We hypothesized that analyzing a representative subset of these previously described ALI‐related transcripts would allow for more precise, objective, and mechanistic evaluation of lung tissue injury and repair before, during, and after EVLP.…”
Section: Introductionmentioning
confidence: 99%